Prevalence and knowledge regarding dental problems among school children, Hoshiarpur, Punjab, India - Singh, Maharaj; Bhattacharjee, T (International Journal of Nursing Research, 2023)
Oral health is an essential component of general health. Good oral health is considered to play role in chewing, aesthetics, and phonetics as well as in personality development. Aim: To assess the prevalence of dental problems and its related knowledge among school children and to find out the association between the knowledge regarding dental problems and the selected demographic variables of school children. Methods: A cross-sectional study was conducted among 150 children aged between 11-13 years studying in the marigold school of district Hoshiarpur, Punjab. The samples were selected through simple random sampling technique. The prevalence of dental problems was assessed by performing clinical examination by using WHO oral health survey method and the knowledge regarding dental problems was assessed through a structured questionnaire. The collected data were analyzed by using descriptive and inferential statistics. Results: The study results regarding the prevalence of dental problems revealed that 82(54.66%) children had dental caries, 53(35.33%) children had dental fluorosis, and 52(34.6%) children had malocclusion problem. The study results regarding knowledge about dental problems show that 52(34.7%) children had poor knowledge, 82(54.6%) children had the average knowledge, 16(10.7%) children had good knowledge and no child had excellent knowledge. The parental education, family income and source of information had an impact on knowledge score of children regarding dental problems. Conclusion: The study findings demonstrate that there is a high prevalence of dental problems and the majority of children had average knowledge regarding dental problems so oral health in schools needs to be intensified and parents should also be educated on oral health so their children will be able to maintain a good oral hygiene.